Triangular-shaped landforms reveal subglacial drainage routes in SW Finland - Makinen J; Kajuutti K; Palmu JP; Ojala A; Ahokangas E (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The aim of this study is to present the first evidence of triangular-shaped till landforms and related erosional features indicative of subglacial drainage within the ice stream bed of the Scandinavian ice sheet in Finland. Previously unidentified grouped patterns of Quaternary deposits with triangular landforms can be recognized from LiDAR-based DEMs. The triangular landforms occur as segments within geomorphologically distinguishable routes that are associated with eskers. The morphological and sedimentological characteristics as well as the distribution of the triangular landforms are interpreted to involve the creep of saturated deforming till, flow and pressure fluctuations of subglacial meltwater associated with meltwater erosion. There are no existing models for the formation of this kind of large-scale drainage systems, but we claim that they represent an efficient drainage system for sub glacial meltwater transfer under high pressure conditions. Our hypothesis is that the routed, large-scale subglacial drainage systems described herein form a continuum between channelized (eskers) and more widely spread small-scale distributed subglacial drainage. Moreover, the transition from the conduit dominated drainage to triangular-shaped subglacial landforms takes place about 50-60 km from the ice margin. We provide an important contribution towards a more realistic representation of ice sheet hydrological drainage systems that could be used to improve paleoglaciological models and to simulate likely responses of ice sheets to increased meltwater production. (C) 2017 Elsevier Ltd. All rights reserved.